Modern calligraphy : learn the beautiful art of brush lettering - Ramos, Maricar Concepcion (Walter Foster Publishing, 2022)
Learn the art of brush lettering with Modern Calligraphy, a step-by-step guide to making personalized, hand-lettered artwork.